Study on the Effect of Micropolar Fluids on the Squeeze Film Elliptical Plates - Anagod, Roopa R. (New Visions in Science and Technology Vol. 7, 2021)
This paper elaborates on the theoretical analysis of squeeze film characteristics between elliptical plates lubricated with non-Newtonian micro-polar fluid on the basis of Eringen's micropolar fluid theory. A subclass of micro fluids is called micropolar fluids which exhibit the micro-rotational effects and micro-rotational inertia also can support couple stress and body couples only. The modified Reynold’s equations governing flow of micro-polar fluid is mathematically derived and the outcome reveals distribution of film pressure which determines the dynamic performance characteristics in terms of load and squeezing time for various values of coupling number and micro structure size parameter. Based on the results reported, the influence of non-Newtonian micropolar fluids is examined in enhancing the time of approach and load carrying capacity to the case of classical Newtonian lubricant. The squeeze film characteristics of elliptical plates are significantly affected in the presence of micro-polar fluid